Earth's atmosphere's lowest layers probed during a lunar eclipse. (19th July 2018) - Kawauchi, Kiyoe; Narita, Norio; Sato, Bun'ei; Hirano, Teruyuki; Kawashima, Yui; Nakamoto, Taishi; Yamashita, Takuya; Tamura, Motohide
Abstract: We report the results of detailed investigation of the Earth's transmission spectra during the lunar eclipse on UT 2011 December 10. The spectra were taken by using the High Dispersion Spectrograph (HDS) mounted on the Subaru 8.2 m telescope with unprecedented resolution in both time and wavelength (300 s exposure time in umbra and 160000 spectral resolution, respectively). In our penumbra and umbra data, we detected the individual absorption lines of $\rm O_2$ and $\rm H_2O$ in transmission spectra and found that they became deeper as the eclipse became deeper. This indicates that the sunlight reaching the Moon passed through lower layers of the Earth's atmosphere with time, because we monitored a given point on the Moon during the full eclipse duration. From the comparison between the observed and theoretically constructed transmission spectra, the lowest altitude at which the sunlight actually passed through the atmosphere is estimated to be about 10 km from the ground, which suggests the existence of sunlight-blocking clouds below that altitude. Our result can be a test case for future investigations of the atmospheric structure of Earth-like exoplanets via transmission spectroscopy including the refraction effect of the planetary atmosphere.